2011
DOI: 10.1074/jbc.m110.176099
|View full text |Cite
|
Sign up to set email alerts
|

A Runx2/miR-3960/miR-2861 Regulatory Feedback Loop during Mouse Osteoblast Differentiation

Abstract: Our recent study showed that miR-2861 promotes osteoblast differentiation by targeting histone deacetylase 5, resulting in increased runt-related transcription factor 2 (Runx2) protein production. Here we identified another new microRNA (miRNA) (miR-3960) that played a regulatory role in osteoblast differentiation through a regulatory feedback loop with miR-2861. miR-3960 and miR-2861 were found clustered at the same loci. miR-3960 was transcribed during bone morphogenic protein 2 (BMP2)-induced osteogenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
168
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(174 citation statements)
references
References 33 publications
(37 reference statements)
3
168
1
2
Order By: Relevance
“…miRNAs play a key role in various biological processes including osteoblast differentiation and mineralization. (29)(30)(31) Osteoclastogenesis is also regulated by miRNAs. In the present study, we performed microarray assays and found miR-148a dramatically upregulated during osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play a key role in various biological processes including osteoblast differentiation and mineralization. (29)(30)(31) Osteoclastogenesis is also regulated by miRNAs. In the present study, we performed microarray assays and found miR-148a dramatically upregulated during osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other clusters have also been studied, such as the auto-regulatory feedback loops controlling Runx2 expression. miR-3960/-2861 is transactivated by Runx2 in vitro, thereby maintaining its own levels of expression by blocking the expression of Hoxa and Hdac5, negative regulators of osteoblast differentiation (Kanzler et al 1998, Dobreva et al 2006, Li et al 2009a, Hu et al 2011. Furthermore, an in vivo approach has demonstrated that Satb2 is also targeted by miR-34s, affecting osteoblast proliferation mainly by means of miR-34b and miR-34c.…”
Section: Mirnas and Osteoblast Differentiationmentioning
confidence: 99%
“…It has also been suggested that a decrease in miR-2861 expression contributes to OP. miR-2861 has already been shown to be a BMP-induced miRNA, targeting Hdac5 and therefore involved in Runx2 degradation (Li et al 2009a, Hu et al 2011. Li et al (2009a) have shown that inhibition of miR-2861, using a specific antisense oligonucleotide introduced by a single tail vein injection, leads to decreased bone mass, reduced osteoblast activity, and osteoblast marker alteration in mice.…”
Section: The Interplay Between Mirnas and Wnt/b-catenin Signalingmentioning
confidence: 99%
“…(8) Our previous studies also identified two new miRNAs (miR-2861/ miR-3960 cluster) in mouse osteoblasts that promoted osteoblast differentiation by repressing histone deacetylase 5 (HDAC5) and homeobox A2 (Hoxa2) expression at the posttranscriptional level. (9,10) However, the functions of miRNAs in osteoblast mineralization need further investigation.…”
mentioning
confidence: 99%